What is the outcome for patients undergoing more than two ileocolonic resections for recurrent Crohn's disease? A comparative study of 569 consecutive procedures. (7th February 2019) - Bouquot, M.; Maggiori, L.; Hain, E.; Prost a la Denise, J.; Bouhnik, Y.; Panis, Y.
Abstract: Aim: To assess the outcome for patients undergoing repeated ileocolonic resection for recurrent Crohn's disease (CD). Method: All patients undergoing ileocolonic resection for terminal ileal CD between 1998 and 2016 in our tertiary care centre were retrospectively reviewed. Results: Between 1998 and 2016, 569 ileocolonic resections were performed for CD: 403 of these were primary resections (1R, 71%), 107 second resections (2R, 19%) and 59 were third (or more) resections (> 2R, 10%). The laparoscopic approach rate was significantly less in the > 2R group (20/59, 34%) compared with the 2R (71/107, 66%; P  = 0.002) and 1R (366/403, 91%) groups. However, conversion to an open approach did not show any difference between the three groups [1R group 46/366 (13%) vs 2R group 14/71 (20%) vs > 2R group 3/20 (15%); 1R vs > 2R P  = 0.750; 2R vs > 2R P  = 0.633]. Postoperative morbidity was significantly increased in the > 2R (28/59, 52%) group compared with the 1R group (115/403, 29%; P  < 0.001) but showed no difference compared with the 2R group (43/107, 40%; P  = 0.365). There was no difference between the groups in the incidence of severe postoperative morbidity (Clavien–Dindo ≥ 3) [1R group n  = 24 (6%); 2R group n  = 6 (6%); > 2R group n  = 4, 7%; 1R vs > 2R P  = 0.865, 2R vs > 2R P  = 0.761]. Conclusion: Although the overall morbidity rate was higher, repeated surgery for recurrent CD in patients undergoing three or more ileocolonic resections was not associated with an increased risk of severe postoperative morbidity in our series.